Implementasi Sistem Manajemen Bandwidth Menggunakan Metode Queue Tree pada Perangkat MikroTik RB941-2nD hAP Lite Series di PT Cilsy Fiolution Indonesia - Hajiar Yuliana; Muhammad Fakhri Abdillah (Department of Electrical Engineering, UNJANI, 2022)
The use of internet networks in human life has become one of the needs in various fields, both offices, government agencies, schools, public services, and others. PT. Cilsy Fiolution Indonesia as one of the startups engaged in the field of information and technology education (Edu-Tech) is very active in the use of the internet, including content creation, uploading videos, office operations, programming, and others. With the limited bandwidth resources available at the office of PT Cilsy Fiolution Indonesia, and with a significant number of active users, it is not uncommon for uneven bandwidth distribution among employees who use internet access, causing problems in working. MikroTik Routerboard is a brand of router devices that has many features. By utilizing the queue tree feature on the MikroTik Router device, bandwidth settings at PT Cilsy Fiolution Indonesia can be based on the port and application protocols commonly used, including HTTP, HTTPS, ICMP, DNS, video streaming, and downloading several types of file extensions. This bandwidth management arrangement aims to equalize the distribution of bandwidth and provide good quality of service for all internet users in the office network of PT Cilsy Fiolution Indonesia.